Origin and evaluation of formation pressures - Sahay, Bhagwan, Dr.; Fertl, Walter H. (Ahmedabad : Allied Publishers, 1988)
On reservoir pressure in oil and gas wells.
Includes bibliographical references and index
Keywords: Reservoir oil pressure